Analysis of efficiency of photodynamic teeth bleaching with the use of photosensitizer chlorine e6 - A. V. Korshunova; V. I. Makarov; A. V. Ryabova; I. D. Romanishkin; O. A. Zorina; E. K. Krechina; G. V. Ponomarev (Biomedical Photonics)
Teeth whitening is one of the most sought-after procedures in aesthetic dentistry. Discolorites that are difficult to whiten, caused by dentin changes or enamel defects, can be eliminated by oxidizing the chromogens with chemical agents that penetrate to the enamel and dentin. In recent years, the method of photodynamic bleaching (PDB) is considered to be minimally invasive. It does not use hydrogen peroxide that leads to increased sensitivity of teeth, and is relatively effective over time. A convenient solution for PDB would be to use chlorin e6 as a photosensitizer, which has a high quantum yield of singlet oxygen generation, low phototoxicity, rapid elimination, on the one hand, and photobleaching capability, on the other. This paper presents quantitative data on the study of the effectiveness of PDB with chlorine e6: color change for 100 teeth after the procedure, chlorine e6 penetration into the tooth tissues, evaluation of the interstitial efficiency of the generation of singlet oxygen and photobleaching of chlorine e6 during laser exposure. It has been statistically established that for one PDB procedure, the tooth color saturation (C) varies on average by 0.5 tones on the VITA scale, and the lightness of color (L) in some cases increases by more than 10 units.